Amniotic band syndrome: a new case report - Mbodji, Aissatou; Wade, Mouhamadou; Gueye, Mamour; Ndiaye, Mame D.; Dia, Aliou D.; Sene, Mouhamed; Sow, Pahté; Gueye, Aminata T.; Mbaye, Magatte (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Amniotic band syndrome is a pathology affecting the extremities of the fetus. It is uncommon with rates around 1 per 10,000 births. The pathophysiology is poorly understood until now with several theories reported in the literature. The diagnosis is most often made at birth. We reported a case of a 40 year old patient with no particular history who had consulted for spontaneous premature rupture of membranes in a 20 weeks pregnancy. The diagnostic of amniotic band syndrome was made after the delivery with amputation of a limb, amniotic syndactilia and deformation of the right foot in equinovarus.